Building Harmony Through Religious Counseling (The Religious Harmony Portrait in North Mamuju) - Muhammad Dachlan; Nur Laili Noviani; Mustolehudin Mustolehudin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
The religious counselor in North Mamuju has a significant role in building harmony in their area. The religious harmony in North Mamuju can be said quite harmonious. We knew this condition by looking at the indication of the religious counselor’s role on guiding and counseling the society. Through qualitative study, this research found some results. First, the moderate counseling model by moslem counselor is proven to improve religious harmony in society. Second, the affection method in Christian doctrine is proven can wreathe the Christian people in develop themselves naturally around moslem society. While in Hindu, the Tri Hita Kirana is used as a model to build religious harmony. The Tri Hita Kirana consists of the concept of relationship with God, with human, and also nature. Through those three model, the religious harmony can be achieved by emphasizing the believing-other attitude also respect and appreciate each other in social and nation life.[Penyuluh agama sebagai ujung tombak Kementerian Agama dalam membangun harmoni di masyarakat memiliki peran penting. Melalui penelitian kualitaif di Kabupaten Mamuju Utara, diperoleh tiga temuan sebagai berikut. Pertama, model penyuluhan secara moderat oleh penyuluh agama Islam, terbukti dapat meningkatkan kerukunan di masyarakat. Kedua, metode kasih dalam ajaran Kristen, mampu menjalin umat kristiani mengembangkan diri di tengah masyarakat muslim secara wajar. Sedangkan dalam agama Hindu, model untuk membangun kerukunan adalah dengan melaksanakan Tri Hita Kirana, yakni hubungan kepada Tuhan, manusia, dan alam. Melalui ketiga model tersebut, kerukunan akan dapat tercapai jika antarumat beragama mengedepankan sikap saling percaya, saling menghormati, dan saling menghargai dalam kehidupan bermasyarakat, berbangsa, dan bernegara.]